Disabling Hip Osteoarthritis and Cardiovascular Pathology: Presence and Impact - Marks, Ray (International Journal of Health, 2013)
Objective: This study examined: 1) the extent to which cases with disabling end-stage hip osteoarthritis would exhibit co-occurring cardiovascular health conditions; 2) the pre and post-surgical impact of the presence of one or more of these health conditions on walking ability. Methods: First, a frequency analysis of the various cardiovascular health conditions listed among 1000 end-stage hip osteoarthritis cases was conducted. Second, a sub-sample of 823 uncomplicated surgical cases was specifically examined. Third, a matched sub-sample of 60 cases with and without co-occurring cardiovascular conditions were compared as regards pain, and their ability to functional physically before and after surgery. Results: Almost 50% of cases initially examined had one or more cardiovascular conditions. Among the 10 categories listed, the most common was high blood pressure, found in 28% cases. Significant (p < .05) associations between having one or more cardiovascular comorbidities and high body mass indices were observed, and co-occurring cardiovascular disease independently predicted walking capacity before and after surgery. Key conclusions: Patients with disabling hip osteoarthritis may exhibit high rates of comorbid cardiovascular health conditions. Those presenting with one or more of cardiovascular condition, may have poorer mobility, both before and after surgery than those with no cardiovascular conditions.